Tumor Exosomal RNAs Promote Lung Pre-metastatic Niche Formation by Activating Alveolar Epithelial TLR3 to Recruit Neutrophils - Liu, Yanfang; Gu, Yan; Han, Yanmei; Zhang, Qian; Jiang, Zhengping; Zhang, Xiang; Huang, Bo; Xu, Xiaoqing; Zheng, Jianming; Cao, Xuetao (Cancer cell, 2016)
The pre-metastatic niche educated by primary tumor-derived elements contributes to cancer metastasis. However, the role of host stromal cells in metastatic niche formation and organ-specific metastatic tropism is not clearly defined. Here, we demonstrate that lung epithelial cells are critical for initiating neutrophil recruitment and lung metastatic niche formation by sensing tumor exosomal RNAs via Toll-like receptor 3 (TLR3). TLR3-deficient mice show reduced lung metastasis in the spontaneous metastatic models. Mechanistically, primary tumor-derived exosomal RNAs, which are enriched in small nuclear RNAs, activate TLR3 in lung epithelial cells, consequently inducing chemokine secretion in the lung and promoting neutrophil recruitment. Identification of metastatic axis of tumor exosomal RNAs and host lung epithelial cell TLR3 activation provides potential targets to control cancer metastasis to the lung. [Display omitted] •TLR3 deficiency reduces lung metastasis in the spontaneous cancer metastatic models•Host TLR3 promotes lung pre-metastatic niche formation via neutrophil recruitment•Tumor exosomal RNAs activate alveolar epithelial TLR3 to induce chemokines•High TLR3 level and neutrophil infiltration in lung cancer predict poor prognosis Liu et al. demonstrate that TLR3 in host alveolar epithelial cells is critical for neutrophil recruitment and lung pre-metastatic niche formation. Mechanistically, small nuclear RNAs from primary tumor-derived exosomes activate TLR3, which leads to chemokine secretion and neutrophil infiltration.